Устройство для определения координаты металлического объекта в массе сырья - Гольдштейн А. Е. Александр Ефремович; Жуков В. К. Владимир Константинович; Калганов С. А.; Коновалов В. Е.
опубл. 23.05.91, Бюл. № 19